A personal encounter with a great scholar - Wan Yusoff, Wan Mazwati (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2021)
My first encounter with him was not in person. Even though at that time I was doing my PhD at the Kulliyyah of Education in IIUM and was studying thinking in Islam. I am very passionate in studying everything I can get my hands on thinking to the extent of willing to pay high price to attend courses on thinking. In 2006, I started to write my proposal and I got hold of a book written by him. This book was the first book written by him that I read and after that I searched for all of his books. The book “Contemplation: An Islamic psychospiritual study” had tremendous impact on me. After I finished reading his book, I felt like both of my feet floated and I was walking on air; feeling incredibly very satisfied. I have never experienced feeling like this reading other books. Words failed to describe my feelings but probably what I did after that could indicate how I felt. I bought 20 units of “Contemplation” and sent to my friends as gifts so that their hearts will always be present in contemplating the materials to be drowned in the majesty of The Spiritual.